2016
DOI: 10.1016/j.ejvs.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based Gene Expression Profiling of Abdominal Aortic Aneurysm

Abstract: This study demonstrates differential expression of transcripts in peripheral blood of individuals with AAA, with functional roles in proteolysis, inflammation, and apoptotic processes. These were modulated by aneurysm exclusion from the circulation and expressed in matched aortic biopsies and smooth muscle cultures. These observations further support the key roles for these pathways in the pathogenesis of AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
(6 reference statements)
2
20
0
Order By: Relevance
“…However, the significance of increased hs-CRP in already established aneurysms is unknown, as inflammation is a multifactorial process. Similar to what we find, other studies reported the role of the immune-related genes and pathways in AOD and AAA disease [55][56][57][58]. In the present study, however, we directly compared AAA and AOD instead of comparing both to a control group, which eliminates all genes that they have in common, or are similarly up-or downregulated.…”
Section: Discussionsupporting
confidence: 65%
“…However, the significance of increased hs-CRP in already established aneurysms is unknown, as inflammation is a multifactorial process. Similar to what we find, other studies reported the role of the immune-related genes and pathways in AOD and AAA disease [55][56][57][58]. In the present study, however, we directly compared AAA and AOD instead of comparing both to a control group, which eliminates all genes that they have in common, or are similarly up-or downregulated.…”
Section: Discussionsupporting
confidence: 65%
“…There have been a few earlier investigations with different study designs using gene expression array analyses from AAA patients, but this is the first study using whole genome microarrays to compare relative mRNA expression patterns between stable and ruptured AAAs in order to identify processes associated with AAA progression and rupture. With our approach we were able to identified and validate 2 gene sets.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal aortic aneurysms (AAAs) are life-threatening diseases that are defined as an abdominal aorta with a diameter > 3 cm or larger than normal [1,2]. This condition occurs with atherosclerosis or plaque build-up, which weakens the walls of the abdominal aorta and results in an outward bulge, similar to a balloon.…”
Section: Introductionmentioning
confidence: 99%